Rethinking systemic change: economic evolution and institutions. Discussion paper - and Cunningham, Shawn; Jenal, Marcus (BEAM Exchange, 2016)
The primary aim of this research project was to find a conceptually sound definition of systemic change. To do so, it was essential to gain a better understanding of how economies change. The central part of the research work, therefore, was an extended literature review on three bodies of knowledge: evolutionary economics new institutional economics complexity theory There is a growing interest in these bodies of knowledge, combined often called New Economic Thinking, and how they affect economic development. Hence, while rethinking systemic change, this work also contributes to answering the broader question of how market systems approaches can contribute to inclusive economic development. The answer, in short, is to shift the focus away from improving transactions at the micro level towards enabling actors to continuously shape an institutional landscape that supports inclusive economic evolution. This discussion paper briefly presents the key messages from the literature review and seven principles drawing from this literature. The principles can be used by market development practitioners, including technical advisers in donor organisations, programme designers and team leaders, to shape programmes and become more in line with how change happens in the economy. A list of selected references is presented at the end. A technical paper contains a much more detailed discussion of the findings and the principles and an extensive list of references. A case study offers a practitioner perspective through the lens of one market systems development programme: DFID-funded Northern Uganda: Transforming the Economy through Climate Smart Agribusiness – Market Development (NUTEC-MD).